The natural history of the chicken [videorecording (DVD)] - Lewis, Mark (Mark T.); Lewis, Mark (Mark T.); Lewis, Mark (Mark T.) (PBS Home Video, 2004)
A series of unusual stories about chickens. Ranges from a woman who revived a chicken with CPR, a man who raises chickens for his own consumption, a woman who keeps a pet chicken, a group of suburbanites who banded together to stop a neighborhood rooster raiser, a headless rooster, and a man who's life changing experience comes when he sees one of his chickens protect her chicks from a hawk.